Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Select the correct choice below and fill in any answer boxes in your choice.

Select The Correct Choice Below And Fill In Any Answer Boxes In Your Choice class=

Sagot :

Given the equation:

[tex](x+7)(x-2)=(x+1)^2[/tex]

We will solve the equation as follows:

[tex]\begin{gathered} (x+7)(x-2)=(x+1)(x+1) \\ x(x-2)+7(x-2)=x(x+1)+1\cdot(x+1) \\ x^2-2x+7x-14=x^2+x+x+1 \\ x^2+5x-14=x^2+2x+1 \end{gathered}[/tex]

Combine the like terms:

[tex]\begin{gathered} x^2-x^2+5x-2x=14+1 \\ 3x=15 \\ x=\frac{15}{3} \\ x=5 \end{gathered}[/tex]

So, the answer will be option A:

The solution set is {5}